Amorphous magnetic particles and preparation method thereof, magnetorheological fluid and preparation method and device thereof
By preparing amorphous magnetic particles with low coercivity and high saturation magnetization intensity, combined with optimized magnetorheological fluid composition and process, the shortcomings of magnetorheological fluid in stability and shear yield stress are solved, and efficient application in magnetic field environment is achieved.
Patent Information
- Application Number
- CN202510696192.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-09-23
AI Technical Summary
Existing magnetorheological fluids are difficult to simultaneously possess high stability, low zero-field viscosity and high shear yield stress under a magnetic field, which limits their application in magnetic field environments.
Amorphous magnetic particles with a coercivity less than 1Oe and a saturation magnetization greater than or equal to 160 emu/g are used. They are prepared through annealing and ball milling processes, combined with crystalline magnetic particles, base fluid, thixotropic agent, dispersant, anti-wear agent and antioxidant to optimize the composition and structure of the magnetorheological fluid.
The magnetorheological fluid can respond quickly in a magnetic field environment, have a high load-bearing capacity and long-term stable operation, reduce the zero-field viscosity, increase the shear yield stress, and enhance the stability and service life of the equipment.
Smart Images

Figure CN120690538A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to amorphous magnetic particles and a preparation method thereof, a magnetorheological fluid and a preparation method and device thereof. Background Art
[0002] Magnetorheological fluids (MR fluids) are intelligent materials composed of magnetic particles (such as iron powder, Fe) uniformly dispersed in a non-magnetic liquid medium. In the absence of an external magnetic field, the magnetic particles in MR fluids are randomly distributed, and their viscosity and yield stress are low. However, upon application of an external magnetic field, their apparent viscosity increases significantly, allowing them to reversibly transform from a linear, viscous fluid with free-flowing properties to a semi-solid material with a controllable yield stress. This ability to alter shear stress in an applied magnetic field offers a variety of potential applications. These tunable rheological properties have led to their widespread use in semi-active vibration dampers.
[0003] An ideal magnetorheological fluid should possess high stability, low zero-field viscosity, and high shear yield stress in a magnetic field. This allows the fluid to quickly respond to magnetic fields, possess high load-bearing capacity, and support long-term stable operation of equipment. However, current magnetorheological fluids struggle to achieve these properties simultaneously, limiting their use.
[0004] Therefore, there is an urgent need for a magnetorheological fluid that has high stability, low zero-field viscosity and high shear yield stress under a magnetic field. Summary of the Invention
[0005] The present invention provides amorphous magnetic particles and a preparation method thereof, a magnetorheological fluid and a preparation method and device thereof. The amorphous magnetic particles have both low coercive force and high saturation magnetization intensity, so that the magnetorheological fluid has high stability, low zero-field viscosity and high shear yield stress under a magnetic field, which is conducive to its rapid response to the magnetic field in a magnetic field environment, high load-bearing capacity and ability to support long-term stable operation of equipment.
[0006] An embodiment of the present invention provides an amorphous magnetic particle, wherein the coercive force of the amorphous magnetic particle is less than 1 Oe; and the saturation magnetization of the amorphous magnetic particle is greater than or equal to 160 emu / g.
[0007] In some embodiments of the present invention, the amorphous magnetic particles include Fe x Si y B z M a , M is selected from one or more elements of Mo, Ni, Co, Cr, Cu, Nb, Ta, W, and P;
[0008] Among them, 78≤x≤85;
[0009] 5≤y≤12;
[0010] 8≤z≤15;
[0011] 0≤a≤3.
[0012] In some embodiments of the present invention, the average particle size of the amorphous magnetic particles is 1 μm to 10 μm;
[0013] An embodiment of the present invention further provides a method for preparing the amorphous magnetic particles as described above, comprising the following steps:
[0014] Annealing the amorphous magnetic particle precursor to obtain the amorphous magnetic particles;
[0015] The amorphous magnetic particle precursor has a coercive force of less than 20 Oe and a saturation magnetization greater than or equal to 160 emu / g;
[0016] In some embodiments of the present invention, the annealing treatment is performed at a temperature of 300° C. to 500° C. and for a time of 70 min to 100 min.
[0017] In some embodiments of the present invention, the annealing treatment further includes performing a first ball milling treatment on the raw materials including the Fe source, the Si source, the B source, and the M source to obtain the amorphous magnetic particle precursor;
[0018] The speed of the first ball milling treatment is 300 rpm to 500 rpm, the ball milling time is 30 h to 60 h, and the ball-to-material ratio is (10-20):1.
[0019] An embodiment of the present invention further provides a magnetorheological fluid comprising crystalline magnetic particles, a base fluid, and the amorphous magnetic particles described in any one of claims 1-3 or the amorphous magnetic particles prepared by the method for preparing the amorphous magnetic particles described in any one of claims 4-6.
[0020] In some embodiments of the present invention, based on the total mass of the crystalline magnetic particles and the amorphous magnetic particles,
[0021] The mass proportion of the crystalline magnetic particles is 50% to 80%;
[0022] And / or, the mass proportion of the amorphous magnetic particles is 20% to 50%.
[0023] In some embodiments of the present invention, the crystalline magnetic particles include one or more of carbonyl iron particles, ferrite particles, cobalt metal particles, nickel metal particles, iron-cobalt alloy particles, iron-nickel alloy particles, and iron nitride particles.
[0024] In some embodiments of the present invention, the magnetorheological fluid further comprises one or more of a thixotropic agent, a dispersant, an anti-wear agent, and an antioxidant;
[0025] Wherein, the thixotropic agent includes one or more of nano-silica, diatomaceous earth, organic bentonite, polyolefin wax, polyfatty acid amide wax, hydrogenated castor oil, polyamide wax, and vinyl chloride compound;
[0026] and / or, the dispersant comprises one or more of oleic acid, stearic acid, titanate, and polyether;
[0027] and / or, the anti-wear agent comprises one or more of graphite, molybdenum disulfide, organic molybdenum compounds, sulfur-phosphorus compounds, chlorophosphorus compounds, chlorosulfur compounds, organic phosphides, and organic metal salts;
[0028] and / or, the antioxidant comprises one or more of an organophosphorus compound, an organomolybdenum compound, an alkylthiocarbamate zinc, a phenolic compound, and a complex compound;
[0029] And / or, the base fluid includes one or more of mineral oil, synthetic hydrocarbon oil, ester oil, silicone oil, natural oil, and fluorinated oil.
[0030] In some embodiments of the present invention, based on the total mass of the magnetorheological fluid,
[0031] The mass proportion of the crystalline magnetic particles and the amorphous magnetic particles is 70% to 85%;
[0032] And / or, the mass proportion of the base liquid is 10% to 20%;
[0033] And / or, the mass proportion of the thixotropic agent is 1.0% to 4.0%;
[0034] And / or, the mass proportion of the dispersant is 0.5% to 3.0%;
[0035] And / or, the mass proportion of the anti-wear agent is 0.3% to 1.5%;
[0036] And / or, the antioxidant accounts for 0.3% to 1.5% by mass.
[0037] In some embodiments of the present invention, the average particle size of the crystalline magnetic particles is 1 μm to 10 μm.
[0038] An embodiment of the present invention further provides a method for preparing the magnetorheological fluid as described above, comprising the following steps:
[0039] The magnetorheological fluid is obtained by subjecting a mixture comprising the amorphous magnetic particles as described above or the amorphous magnetic particles prepared by the method for preparing the amorphous magnetic particles as described above, crystalline magnetic particles, and a base fluid to a second ball milling process.
[0040] In some embodiments of the present invention, the speed of the second ball milling treatment is 300 rpm~500 rpm, the treatment time is 2~10 hours, and the ball-to-material ratio is (1~5):1.
[0041] An embodiment of the present invention further provides a device comprising the magnetorheological fluid as described above or the magnetorheological fluid prepared by the magnetorheological fluid preparation method as described above.
[0042] The amorphous magnetic particles provided in the embodiment of the present invention have a coercive force of less than 1 Oe and a saturation magnetization greater than or equal to 160 emu / g. They have both low coercive force and high saturation magnetization, so that the magnetorheological fluid has high stability, low zero-field viscosity and high shear yield stress under a magnetic field. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0044] Figure 1 A schematic diagram of the atomic arrangement of amorphous magnetic particles provided in an embodiment of the present invention;
[0045] Figure 2 This is the XRD diffraction pattern of the amorphous magnetic particles provided in Example 2 of the present invention.
[0046] The above drawings illustrate specific embodiments of the present invention, which will be described in more detail below. These drawings and the accompanying description are not intended to limit the scope of the present invention in any way, but rather to illustrate the concept of the present invention to those skilled in the art by reference to specific embodiments. DETAILED DESCRIPTION
[0047] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.
[0048] Currently, magnetorheological fluids have the problem of being difficult to simultaneously achieve high stability, low zero-field viscosity, and high shear yield stress under a magnetic field.
[0049] The inventors have discovered through research that these properties are closely related to the properties of the magnetic particles in the MRF. For example, the type and coercivity of the magnetic particles affect the stability and low zero-field viscosity of the MRF, while the saturation magnetization of the magnetic particles significantly influences the MRF's shear yield stress under a magnetic field. However, the magnetic particles in current MRFs lack both low coercivity and high saturation magnetization, making it impossible for the MRF to achieve both high stability, low zero-field viscosity, and high shear yield stress under a magnetic field.
[0050] Based on this, an embodiment of the present invention provides an amorphous magnetic particle, wherein the coercive force of the amorphous magnetic particle is less than 1 Oe; and the saturation magnetization of the amorphous magnetic particle is greater than or equal to 160 emu / g.
[0051] When the amorphous magnetic particles of the embodiment of the present invention have the above-mentioned composition and properties, the magnetorheological fluid can have high stability, low zero-field viscosity and high shear yield stress under a magnetic field.
[0052] In detail, the amorphous magnetic particles of the embodiment of the present invention have both small coercive force and high saturation magnetization, so that the magnetorheological fluid has strong stability, low zero-field viscosity and high shear yield stress performance under magnetic field. Specifically, Figure 1 As shown, when the amorphous magnetic particles have the above-mentioned coercive force, the irregularity of the atomic arrangement inside them is further increased, so they contain more suitable microscopic voids or so-called "free volumes". These suitable spaces enable the amorphous magnetic particles to have a suitable effective density (7.0 g / cm³, lower than the density of carbonyl iron powder 7.8 g / cm³), so that the overall magnetic particles can exist stably in the magnetorheological fluid, improving the problem of sedimentation under zero field. The amorphous structure in the embodiment of the present invention also has a low oxidation tendency and magnetic stability at high temperatures, which improves the stability of the magnetorheological fluid under different working conditions and can support long-term operation of the equipment. At the same time, the amorphous magnetic particles in the embodiment of the present invention have a low coercive force, and the grain boundaries are further weakened, making the magnetic domain walls easier to move. At the same time, since the structural disorder of the amorphous magnetic particles in the embodiment of the present invention is further reduced, the magnetocrystalline anisotropy is almost zero, and they will not be fixed under the action of an external magnetic field. In a specific direction, after the magnetic field is removed, the magnetic domain can quickly return to the initial disordered state, which can ensure that the magnetorheological fluid is easy to magnetize and demagnetize, reduce the hysteresis effect, reduce energy loss, and make the magnetorheological fluid have a lower low zero-field viscosity in dynamic operation, so that the magnetorheological fluid can have a better response speed in the magnetic field; the amorphous magnetic particles in the embodiment of the present invention also have a higher saturation magnetization intensity, which helps the magnetorheological fluid to form a stronger magnetic chain structure in the magnetic field environment, thereby increasing the shear yield stress, so that the magnetorheological fluid has a higher bearing capacity and strength in the magnetic field to adapt to the operation of the equipment under different conditions.
[0053] The crystalline magnetic particles and amorphous magnetic particles in the embodiments of the present invention may be spherical or quasi-spherical in shape, and the shape may be selected according to actual conditions.
[0054] In the embodiments of the present invention, the coercivity and saturation magnetization of the amorphous magnetic particles can be tested using a vibrating sample magnetometer. Specifically, the amorphous magnetic particles in the embodiments and comparative examples are first separated using high-speed centrifugation, ultrasonically cleaned with ethyl acetate or n-hexane, and then dried in a vacuum oven at 80°C. A vibrating sample magnetometer is then used to measure the magnetic properties of the samples, controlling the sample mass to 50 mg, the batch error to <1%, and the magnetic field range to ±13,000 Oe. The hysteresis loops of the sample magnetic properties are then analyzed and processed to determine the saturation magnetization and coercivity of the amorphous magnetic particles in the embodiments and comparative examples.
[0055] In some embodiments of the present invention, the amorphous magnetic particles include Fe x Si y B z M a M is selected from one or more elements selected from Mo, Ni, Co, Cr, Cu, Nb, Ta, W, and P; wherein 78 ≤ x ≤ 85; 5 ≤ y ≤ 12; 8 ≤ z ≤ 15; and 0 ≤ a ≤ 3. Specifically, when the amorphous magnetic particles include Fe, Si, and B, they are more likely to form an amorphous structure. When the amorphous magnetic particles also include M, their coercivity and saturation magnetic strength are further improved.
[0056] In detail, when the amorphous magnetic particles include Fe element and the atomic percentage x of Fe element is controlled to be 78≤x≤85, the saturation magnetic strength of the amorphous magnetic particles can be further improved; when the amorphous magnetic particles include Si element and the atomic percentage y of Si element is controlled to be 5≤y≤12, the magnetocrystalline anisotropy of the amorphous magnetic particles is further reduced, the movement of the magnetic domain wall is further improved, and the coercive force is further reduced; when the amorphous magnetic particles include Si element and the atomic percentage z of Si element is controlled to be 8≤x≤15, the amorphous forming ability of the amorphous magnetic particles can be further improved, the coercive force is further reduced, and at the same time, the mechanical properties (such as strength and hardness) of the amorphous magnetic particles can be better taken into account.
[0057] In some embodiments, the amorphous magnetic particles further include an M element. When the atomic percentage a of the M element is 0 ≤ x ≤ 3, both the coercivity and saturation magnetic strength can be further improved. The M element can be selected from one of Mo, Ni, Co, Cr, Cu, Nb, Ta, W, and P, or can be selected from a plurality of these elements. Specifically, when the M element includes the Mo element, it is beneficial to further enhance the amorphous forming ability of the amorphous magnetic particles, further reduce crystallization, and better improve the high temperature stability and oxidation resistance of the material; when the M element includes the Ni element, it is beneficial to further reduce the coercive force of the amorphous magnetic particles, further optimize their soft magnetic properties, and is more beneficial to improve the corrosion resistance of the amorphous magnetic particles; when the M element includes the Co element, it is beneficial to further enhance the saturation magnetization of the amorphous magnetic particles; when the M element includes the Cr element, it is beneficial to further balance the improvement of the corrosion resistance and coercive force of the amorphous magnetic particles; when the M element includes the Cu element, it is beneficial to further promote the uniformity of the amorphous magnetic particles and enhance the amorphous forming ability; when the M element includes the Nb and P elements, it is beneficial to further inhibit the crystallization of the magnetic particles and significantly enhance the amorphous forming ability; when the M element includes the Ta and W elements, it is beneficial to further improve the high temperature resistance and oxidation resistance of the amorphous magnetic particles.
[0058] In some embodiments, the average particle size of the amorphous magnetic particles is between 1 μm and 10 μm. For example, the average particle size of the amorphous magnetic particles (also referred to as D50 in the present invention) is 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, or a range consisting of any two thereof. The present embodiments further enhance the stability of the magnetorheological fluid by further controlling the average particle size of the amorphous magnetic particles. The average particle size of the amorphous magnetic particles in the embodiments of the present invention can be measured using conventional testing methods and instruments, such as a particle size analyzer.
[0059] An embodiment of the present invention further provides a method for preparing amorphous magnetic particles, comprising the following steps:
[0060] Annealing the amorphous magnetic particle precursor to obtain amorphous magnetic particles;
[0061] The amorphous magnetic particle precursor has a coercive force less than 20 Oe and a saturation magnetization greater than or equal to 160 emu / g.
[0062] The amorphous magnetic particles formed from the amorphous magnetic particle precursor according to embodiments of the present invention after annealing have a coercivity of less than 1 Oe and a saturation magnetization greater than or equal to 160 emu / g. Specifically, annealing can effectively release internal stress in the amorphous magnetic particles, further increasing the degree of amorphization of the amorphous magnetic particles, effectively reducing the coercivity while maintaining a high saturation magnetization of the amorphous magnetic particles.
[0063] In some embodiments, when the annealing temperature is 300°C to 500°C and the annealing time is 70 minutes to 100 minutes, the resulting magnetorheological fluid exhibits higher stability, lower zero-field viscosity, and higher shear yield stress under a magnetic field. For example, the annealing temperature is 300°C, 400°C, 500°C, or a range consisting of any two thereof; and the annealing time is 70 minutes, 80 minutes, 90 minutes, 100 minutes, or a range consisting of any two thereof.
[0064] It should be noted that the annealing process also includes naturally cooling the heated product. After natural cooling, the annealed product is screened to reduce the average particle size of the amorphous magnetic particles to 1-10 μm. It should be noted that, in order to improve the purity of the amorphous magnetic particles, in some embodiments, the annealing process is performed in an inert atmosphere.
[0065] In some embodiments, prior to the annealing process, the raw materials including the Fe source, Si source, B source, and M source are subjected to a first ball milling process to obtain an amorphous magnetic particle precursor. Specifically, the embodiments of the present invention can further improve both the coercivity and saturation magnetization of the amorphous magnetic particles by controlling the feed ratio of the Fe source, Si source, and B source. By controlling the type and feed ratio of the M element, the amorphous magnetic particles can further exhibit better corrosion resistance, high-temperature stability, low coercivity, and high saturation magnetization.
[0066] In an embodiment of the present invention, the first ball milling process is performed at a speed of 300 rpm to 500 rpm, a ball milling time of 30 h to 60 h, and a ball-to-material ratio of (10-20):1, which is advantageous for obtaining a magnetorheological fluid having high stability, low zero-field viscosity, and high shear yield stress in a magnetic field. For example, the first ball milling process is performed at a speed of 300 rpm, 400 rpm, 500 rpm, or a range consisting of any two thereof; the first ball milling process is performed for a time of 30 h, 40 h, 50 h, 60 h, or a range consisting of any two thereof; and the ball-to-material ratio is performed at a speed of 10:1, 15:1, 20:1, or a range consisting of any two thereof.
[0067] It should be clarified that during the first ball milling process, in order to better obtain a magnetorheological fluid with high stability, low zero-field viscosity and high shear yield stress under a magnetic field, the first ball milling process can be carried out in an inert atmosphere (such as argon) or in a vacuum atmosphere.
[0068] The embodiment of the present invention does not impose any special limitation on the temperature of the first ball milling process, and the temperature can be selected according to actual conditions.
[0069] An embodiment of the present invention further provides a magnetorheological fluid, comprising crystalline magnetic particles, a base fluid, and the aforementioned amorphous magnetic particles or amorphous magnetic particles prepared by the aforementioned method for preparing amorphous magnetic particles.
[0070] The magnetorheological fluid of the embodiment of the present invention has high stability, low zero-field viscosity and high shear yield stress under a magnetic field.
[0071] The inventors found that by controlling the mass ratio of crystalline magnetic particles and amorphous magnetic particles in the magnetic particles, the stability, low zero-field viscosity and high shear yield stress under a magnetic field of the magnetorheological fluid can be further improved.
[0072] In some embodiments, the mass proportion of the crystalline magnetic particles is 50% to 80% based on the total mass of the crystalline magnetic particles and the amorphous magnetic particles. For example, the mass proportion of the crystalline magnetic particles is 50%, 60%, 70%, 80% or a range consisting of any two thereof.
[0073] In some embodiments, based on the total mass of the crystalline magnetic particles and the amorphous magnetic particles, the mass proportion of the amorphous magnetic particles is 20% to 50%. For example, the mass proportion of the amorphous magnetic particles is 20%, 30%, 40%, 50% or a range consisting of any two thereof.
[0074] In some embodiments of the present invention, the crystalline magnetic particles include one or more of carbonyl iron particles, ferrite particles, cobalt metal particles, nickel metal particles, iron-cobalt alloy particles, iron-nickel alloy particles, and iron nitride. By using these crystalline magnetic particles, the magnetorheological fluid can exhibit improved high shear yield stress under a magnetic field.
[0075] In addition, in order to further improve the stability of the crystalline magnetic particles, in some embodiments of the present invention, the magnetorheological fluid further includes one or more of a thixotropic agent, a dispersant, an anti-wear agent, and an antioxidant.
[0076] In some embodiments, the thixotropic agent includes one or more of nanosilica, diatomaceous earth, organic bentonite, polyolefin wax, polyfatty acid amide wax, hydrogenated castor oil, polyamide wax, and vinyl chloride compounds. These thixotropic agents can better form a network structure in the magnetorheological fluid, further improving the stability of the magnetorheological fluid.
[0077] In some embodiments, the dispersant includes one or more of oleic acid, stearic acid, titanate, and polyether. These dispersants can evenly distribute the crystalline and amorphous magnetic particles in the magnetorheological fluid, thereby mitigating sedimentation caused by magnetic particle aggregation and further enhancing the stability of the magnetorheological fluid. The thixotropic agent can be synthesized using conventional methods or commercially available products.
[0078] In some embodiments, the antiwear agent includes one or more of graphite, molybdenum disulfide, an organic molybdenum compound, a sulfur-phosphorus compound, a chlorophosphorus compound, a chlorosulfur compound, an organic phosphide, and an organic metal salt. These antiwear agents can effectively protect the surfaces of the magnetic particles and mechanical components within the device, thereby enhancing the stability of the magnetorheological fluid and extending the service life of the device. The above-mentioned anti-wear agent can use a conventional magnetorheological fluid anti-wear agent. For example, the organic molybdenum compound includes but is not limited to at least one of molybdenum dithiocarbamate (MoDTC) and molybdenum dialkyl dithiophosphate; the sulfur-phosphorus compound includes but is not limited to one or more of zinc dialkyl dithiophosphate (ZDDP), triphenyl thiophosphate, and sulfur-phosphorized polyolefin; the chlorophosphorus compound includes but is not limited to trichloroethyl phosphate (TCEP); the chlorosulfur compound includes but is not limited to one or more of chloroalkyl zinc thiophosphate and chlorinated paraffin; the organic phosphorus compound includes but is not limited to one or more of triphenyl phosphate, trioctyl phosphate, dibutyl dithiophosphate (such as zinc dibutyl dithiophosphate ZDBP), and isopropylated triphenyl phosphate; the organic metal salt includes but is not limited to one or more of calcium alkyl salicylate, calcium alkyl sulfonate, and borate.
[0079] In some embodiments, the antioxidant includes one or more of an organophosphorus compound, an organomolybdenum compound, an alkylthiocarbamate zinc, a phenolic compound, and a complex compound. For example, the organophosphorus compound includes, but is not limited to, one or more of trialkyl phosphates, phosphites, zinc dialkyldithiophosphates, and zinc dithiophosphates; the organomolybdenum compound includes, but is not limited to, one or more of molybdenum dithiocarbamates and molybdenum dialkyldithiophosphates; the alkylthiocarbamate zinc includes, but is not limited to, at least one of zinc dibutyldithiocarbamate and zinc diethyldithiocarbamate; the phenolic compound includes, but is not limited to, one or more of 2,6-di-tert-butyl-p-cresol, 4,4'-methylenebis(2,6-di-tert-butylphenol), octylbutyldiphenylamine, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and trisnonylated phenol; and the complex compound includes, but is not limited to, one or more of alkyldiphenylamine and thiodipropionate.
[0080] In some embodiments, the base fluid includes one or more of mineral oil, synthetic hydrocarbon oil (such as poly-α-olefin), ester oil (such as diester and polyester oil), silicone oil, natural oil, and fluoro oil. These base fluids have improved stability, which helps to further enhance the stability of the magnetorheological fluid.
[0081] In order to better balance improving the stability, low zero-field viscosity, and high shear yield stress of the magnetorheological fluid under a magnetic field, the embodiment of the present invention further limits the mass ratio of each component in the magnetorheological fluid.
[0082] In some embodiments, based on the total mass of the magnetorheological fluid, the mass proportion of the crystalline magnetic particles and the amorphous magnetic particles is 70% to 85%. For example, the mass proportion of the crystalline magnetic particles and the amorphous magnetic particles is, for example, 70%, 75%, 80%, 85% or a range consisting of any two thereof.
[0083] In some embodiments, the base fluid accounts for 10% to 20% of the total mass of the magnetorheological fluid. For example, the base fluid accounts for 10%, 15%, 20% or any two thereof.
[0084] In some embodiments, the mass proportion of the thixotropic agent is 1.0% to 4.0% based on the total mass of the magnetorheological fluid. For example, the mass proportion of the thixotropic agent is 1%, 2%, 3%, 4% or any two thereof.
[0085] In some embodiments, the mass proportion of the dispersant is 0.5% to 3.0% based on the total mass of the magnetorheological fluid. For example, the mass proportion of the dispersant is 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any two thereof.
[0086] In some embodiments, the mass proportion of the anti-wear agent is 0.3% to 1.5% based on the total mass of the magnetorheological fluid. For example, the mass proportion of the anti-wear agent is 0.3%, 0.5%, 1%, 1.5%, or a range consisting of any two thereof.
[0087] In some embodiments, the antioxidant accounts for 0.3% to 1.5% by mass based on the total mass of the magnetorheological fluid. For example, the antioxidant accounts for 0.3%, 0.5%, 1%, 1.5%, or any two thereof.
[0088] Some embodiments of the present invention further enhance the stability of the magnetorheological fluid by controlling the particle size of the crystalline magnetic particles. In some embodiments of the present invention, the particle size of the crystalline magnetic particles is 1 μm to 10 μm. For example, the particle size of the crystalline magnetic particles is 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, or any combination thereof.
[0089] An embodiment of the present invention also provides a method for preparing the above-mentioned magnetorheological fluid, comprising the following steps: subjecting a mixture of the above-mentioned amorphous magnetic particles or amorphous magnetic particles prepared by the above-mentioned method for preparing amorphous magnetic particles, crystalline magnetic particles, and a base fluid to a second ball milling treatment to obtain a magnetorheological fluid.
[0090] The magnetorheological fluid prepared by the embodiment of the present invention by mixing the amorphous magnetic particles having the special coercive force and saturation magnetic ring strength with crystalline magnetic particles and a base fluid has high stability, low zero-field viscosity and high shear yield stress under a magnetic field.
[0091] To achieve a more uniform dispersion of the components in the magnetorheological fluid, some embodiments of the present invention further include an energy-saving mixing treatment of the amorphous magnetic particles, crystalline magnetic particles, and base fluid prior to the second ball milling process. The present embodiments do not impose specific restrictions on the method and duration of the mixing treatment, which can be selected based on actual conditions. For example, the stirring speed can be set at 800-1000 rpm at a temperature of 50°C, and the mixture of amorphous magnetic particles, crystalline magnetic particles, and base fluid can be stirred for 60 minutes.
[0092] The present invention does not impose any particular restrictions on the average particle size of the raw materials, and may be selected based on actual needs. In one embodiment, the average particle size of the raw materials is 10 μm to 50 μm. The present invention also does not impose any particular restrictions on the purity of the raw materials, and may be selected based on actual conditions.
[0093] In some embodiments, the second ball milling process is performed at a speed of 300 rpm to 500 rpm, for a processing time of 2 to 10 hours, and at a ball-to-material ratio of (1 to 5): 1.
[0094] The embodiment of the present invention does not impose any special limitation on the temperature of the second ball milling process, and the temperature can be selected according to actual conditions.
[0095] This is advantageous for obtaining a magnetorheological fluid having both high stability, low zero-field viscosity, and high shear yield stress in a magnetic field. For example, the second ball milling time is 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, or any two thereof; the second ball milling speed is 300 rpm, 400 rpm, 500 rpm, or any two thereof; and the ball-to-material ratio is 1:1, 2:1, 3:1, 4:1, 5:1, or any two thereof.
[0096] In some embodiments of the present invention, the mixture further comprises one or more of a thixotropic agent, a dispersant, an anti-wear agent, and an antioxidant, which facilitates the preparation of a magnetorheological fluid with improved stability. The selection of the thixotropic agent, dispersant, anti-wear agent, and antioxidant is as described above and will not be further elaborated here.
[0097] An embodiment of the present invention further provides a device comprising the magnetorheological fluid or the magnetorheological fluid prepared by the method for preparing the magnetorheological fluid. The device has advantages corresponding to those of the magnetorheological fluid, which will not be described in detail here.
[0098] The above-mentioned devices may include but are not limited to automobiles, various shock absorbers, clutches, brakes, micro-motion stages in optical instruments and semiconductor manufacturing equipment, medical rehabilitation equipment, flexible clamps, vacuum sealing devices, tactile devices, etc.
[0099] The technical solution of the present invention is further described below with reference to specific embodiments.
[0100] Example 1
[0101] The magnetorheological fluid of this embodiment is prepared by the following steps:
[0102] 1) A raw material including 85 g of pure iron (Fe source, purity 99.99 wt.%), 5 g of silicon (Si source, purity 99.95 wt.%), 8 g of boron (B source, purity 99.95 wt.%), and 2 g of molybdenum (M source, purity 99.95 wt.%) was subjected to a first ball milling treatment under an inert atmosphere (argon) at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm for 45 hours to obtain an amorphous magnetic particle precursor.
[0103] 2) The amorphous magnetic particle precursor is annealed in an argon atmosphere at 400° C. for 90 minutes, and naturally cooled to obtain amorphous magnetic particles; the amorphous magnetic particles are then sieved (500 mesh).
[0104] 3) The amorphous magnetic particles, crystalline magnetic particles (carbonyl iron), base fluid (poly-α-olefin), thixotropic agent (organic bentonite), dispersant (oleic acid), anti-wear agent (molybdenum disulfide), and antioxidant (zinc dialkyl dithiophosphate) were stirred at a temperature of 50° C. and a speed of 900 rpm for 60 minutes to obtain a mixture. Stainless steel grinding balls were added to the mixture at a mass ratio of the mixture to the grinding balls of 1:2, and the mixture was subjected to a second ball milling treatment at a speed of 400 rpm for 5 hours to obtain a magnetorheological fluid.
[0105] The coercive force of the amorphous magnetic particles of this embodiment (coercive force in the table), the saturation magnetization of the amorphous magnetic particles (saturation magnetization in the table), the chemical formula composition of the amorphous magnetic particles (amorphous magnetic particles in the table), the mass proportion of the amorphous magnetic particles (based on the total mass of the crystalline magnetic particles and the amorphous magnetic particles), the mass proportion of the crystalline magnetic particles (based on the total mass of the crystalline magnetic particles and the amorphous magnetic particles), the mass proportion of the crystalline magnetic particles and the amorphous magnetic particles (based on the total mass of the magnetorheological fluid, the mass proportion of the magnetic particles in the table), the mass proportion of the base fluid (based on the total mass of the magnetorheological fluid), the mass proportion of the thixotropic agent (based on the total mass of the magnetorheological fluid), the mass proportion of the dispersant (based on the total mass of the magnetorheological fluid), the mass proportion of the anti-wear agent (based on the total mass of the magnetorheological fluid), the mass proportion of the antioxidant (based on the total mass of the magnetorheological fluid), the average particle size of the crystalline magnetic particles, and the average particle size of the amorphous magnetic particles are shown in Tables 1 and 2.
[0106] Example 2
[0107] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, 11g boron, and 2g molybdenum.
[0108] Example 3
[0109] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 78g pure iron, 5g silicon, 15g boron, and 2g molybdenum.
[0110] Example 4
[0111] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 8g silicon, 8g boron, and 2g nickel.
[0112] Example 5
[0113] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 78g pure iron, 12g silicon, 8g boron, and 2g cobalt.
[0114] Example 6
[0115] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, 12g boron, and 1g molybdenum.
[0116] Example 7
[0117] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, 10g boron, and 3g molybdenum.
[0118] Example 8
[0119] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, 11g boron, and 2g molybdenum.
[0120] Example 9
[0121] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, 11g boron, and 2g nickel.
[0122] Example 10
[0123] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, 11g boron, and 2g chromium.
[0124] Example 11
[0125] This embodiment is basically the same as embodiment 2, except that the mass proportion of carbonyl iron powder in the magnetorheological fluid in this embodiment is 64%, and the amorphous magnetic particles Fe 82 Si5B 11 Mo2 accounts for 64% of the mass.
[0126] Example 12
[0127] This embodiment is basically the same as embodiment 2, except that the mass proportion of carbonyl iron powder in the magnetorheological fluid in this embodiment is 40%, and the amorphous magnetic particles Fe 82 Si5B 11 Mo2 accounts for 40% of the mass.
[0128] Examples 13-19 differ in the following parameters: the mass percentage of amorphous magnetic particles (based on the total mass of the crystalline and amorphous magnetic particles), the mass percentage of crystalline magnetic particles (based on the total mass of the crystalline and amorphous magnetic particles), the mass percentage of crystalline magnetic particles and amorphous magnetic particles (based on the total mass of the magnetorheological fluid, which is the mass percentage of magnetic particles in the table), the mass percentage of base fluid (based on the total mass of the magnetorheological fluid), the mass percentage of thixotropic agent (based on the total mass of the magnetorheological fluid), the mass percentage of dispersant (based on the total mass of the magnetorheological fluid), the mass percentage of anti-wear agent (based on the total mass of the magnetorheological fluid), the mass percentage of antioxidant (based on the total mass of the magnetorheological fluid), the average particle size of the crystalline magnetic particles, and the average particle size of the amorphous magnetic particles. See Tables 1 and 2 for details. Furthermore, the coercivity and saturation magnetization of the amorphous magnetic particles in each example are shown in Table 1.
[0129] Example 20
[0130] This embodiment is basically the same as Example 1, except that the raw materials of this embodiment are 82g pure iron, 5g silicon, and 13g boron.
[0131] Comparative Example 1
[0132] This comparative example is basically the same as Example 1, except that the raw materials of this comparative example are 86g pure iron, 5g silicon, 7g boron and 2g molybdenum.
[0133] Comparative Example 2
[0134] This comparative example is basically the same as Example 1, except that the raw materials of this comparative example are 77g pure iron, 5g silicon, 16g boron and 2g molybdenum.
[0135] Comparative Example 3
[0136] This comparative example is basically the same as Example 1, except that the raw materials of this comparative example are 86g pure iron, 4g silicon, 8g boron and 2g molybdenum.
[0137] Comparative Example 4
[0138] This comparative example is basically the same as Example 1, except that the raw materials of this comparative example are 77g pure iron, 13g silicon, 8g boron and 2g molybdenum.
[0139] Comparative Example 5
[0140] This comparative example is basically the same as Example 1, except that the raw materials of this comparative example are 75g pure iron, 5g silicon, 16g boron and 4g molybdenum.
[0141] Comparative Example 6
[0142] This comparative example is basically the same as Example 1, except that the magnetic particles in this comparative example are carbonyl iron powder particles with a D50 particle size of 5.0 μm.
[0143] Comparative Example 7
[0144] This comparative example is basically the same as Example 2, except that the magnetic particles in this comparative example are 80gFe 82 Si5B 11 Mo2 amorphous magnetic particles.
[0145]
[0146]
[0147] Test example
[0148] Conventional XRD was used to test Example 2, and the test results were as follows: Figure 2 As shown. Figure 2 It can be seen that the broad band between 30° and 60° indicates that the interior of the amorphous magnetic particles is an amorphous structure.
[0149] The coercivity and saturation magnetic strength of the amorphous magnetic particles in the Examples and Comparative Examples were tested. Specifically, the amorphous magnetic particles in the Examples and Comparative Examples were separated using high-speed centrifugation, ultrasonically cleaned with ethyl acetate or n-hexane, and then dried in a vacuum oven at 80°C. The vibrating sample magnetometer method was then used to measure the magnetic properties of the samples, controlling the sample mass to 50 mg, with a batch error of less than 1%, and setting the magnetic field range to ±13,000 Oe. The hysteresis loops of the magnetic properties of the samples were obtained. Analysis of the hysteresis loops revealed the saturation magnetization and coercivity of the amorphous magnetic particles in the Examples and Comparative Examples. The results are shown in Table 3.
[0150] The magnetorheological fluids of the examples and comparative examples were subjected to sedimentation rate tests, magnetorheological performance tests, and magnetorheological fluid durability tests with reference to JB / T 12512-2015.
[0151] Sedimentation rate test: Each set of magnetorheological fluid was placed in a 25 mL graduated cylinder, sealed, and allowed to stand at 25°C. The height of the supernatant was observed at the same time each day. The sedimentation rate is the ratio of the supernatant height to the total height (25 mL). The test lasted 30 days. The results are shown in Table 3 (30-day sedimentation rate).
[0152] Magnetorheological properties testing: The zero-field viscosity of each magnetorheological fluid and the shear yield stress of the slurry under a 0.3 T magnetic field were tested on a rheometer according to the set program. The results are shown in Table 3 (zero-field viscosity and 0.3 T shear yield stress).
[0153] Durability testing of magnetorheological fluids: Each set of magnetorheological fluids was exposed to air at 80°C. After 60 days, samples were taken and the shear yield stress of the slurry was tested according to a pre-set procedure under a magnetic field. The results are shown in Table 3 (shear yield stress after 60 days).
[0154]
[0155] As can be seen from the table, compared to the comparative examples, the examples of the present invention all exhibit lower sedimentation rates and zero-field viscosities, while also exhibiting higher shear yield stresses at a 0.3T magnetic field. Furthermore, after a 60-day durability test, the shear yield stress decreased by ≤5%, demonstrating a low oxidation tendency and magnetic stability at high temperatures, thereby improving the stability of the magnetorheological fluid under various operating conditions. In Examples 1-3, the Fe content in the amorphous magnetic particles affected the overall saturation magnetization, resulting in a decrease in the shear yield stress at a 0.3T magnetic field. Compared to Example 2, the shear yield stress at a 0.3T magnetic field was higher in Example 9 with Co addition, while the shear yield stress of the Cr addition in Example 10 remained essentially unchanged after the durability test. Compared to Example 2, in Examples 11 and 12, the increase or decrease in the carbonyl iron powder content also affected the shear yield stress at a 0.3T magnetic field of the corresponding magnetorheological fluid. With the increase in carbonyl iron powder, the shear yield stress at a 0.3T magnetic field of the magnetorheological fluid also increased, but at the same time, the zero-field viscosity and sedimentation rate also increased. The amorphous magnetic particles in Comparative Examples 1 and 3 are crystalline materials with high coercivity, exhibiting similar trends to Comparative Example 6: high zero-field viscosity and a shear yield stress of less than 25 kPa at a 0.3 T magnetic field. Furthermore, the shear yield stress decreases by 30% after 60 days, indicating a high tendency to oxidize and low magnetic stability at high temperatures, resulting in poor stability. Comparative Examples 2, 4, 5, and 7 also exhibit low sedimentation rates and zero-field viscosities, but due to their low Fe content, their overall saturation magnetization is low, resulting in lower absolute values of shear yield stress.
[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An amorphous magnetic particle, characterized in that The coercive force of the amorphous magnetic particles is less than 1 Oe; and the saturation magnetization of the amorphous magnetic particles is greater than or equal to 160 emu / g.
2. The amorphous magnetic particle according to claim 1, characterized in that The amorphous magnetic particles include Fe x Si y B z M a , M is selected from one or more elements of Mo, Ni, Co, Cr, Cu, Nb, Ta, W, and P; Among them, 78≤x≤85; 5≤y≤12; 8≤z≤15; 0≤a≤3。 3. The amorphous magnetic particle according to claim 1 or 2, characterized in that The average particle size of the amorphous magnetic particles is 1 μm to 10 μm.
4. A method for preparing the amorphous magnetic particles according to any one of claims 1 to 3, characterized in that: The steps include: Annealing the amorphous magnetic particle precursor to obtain the amorphous magnetic particles; The amorphous magnetic particle precursor has a coercive force less than 20 Oe and a saturation magnetization greater than or equal to 160 emu / g.
5. The method for preparing amorphous magnetic particles according to claim 4, characterized in that: The annealing treatment is performed at a temperature of 300° C. to 500° C. and for a time of 70 min to 100 min.
6. The method for preparing amorphous magnetic particles according to claim 4 or 5, characterized in that: Before the annealing treatment, the raw materials including Fe source, Si source, B source and M source are subjected to a first ball milling treatment to obtain the amorphous magnetic particle precursor; The speed of the first ball milling treatment is 300 rpm to 500 rpm, the ball milling time is 30 h to 60 h, and the ball-to-material ratio is (10-20):
1.
7. A magnetorheological fluid, characterized in that: The invention comprises crystalline magnetic particles, a base liquid, the amorphous magnetic particles according to any one of claims 1 to 3, or the amorphous magnetic particles prepared by the preparation method of the amorphous magnetic particles according to any one of claims 4 to 6.
8. The magnetorheological fluid according to claim 7, characterized in that Based on the total mass of the crystalline magnetic particles and the amorphous magnetic particles, The mass proportion of the crystalline magnetic particles is 50% to 80%; And / or, the mass proportion of the amorphous magnetic particles is 20% to 50%.
9. The magnetorheological fluid according to any one of claims 7 or 8, characterized in that: The crystalline magnetic particles include one or more of carbonyl iron particles, ferrite particles, cobalt metal particles, nickel metal particles, iron-cobalt alloy particles, iron-nickel alloy particles, and iron nitride particles.
10. The magnetorheological fluid according to any one of claims 7 to 9, characterized in that: The magnetorheological fluid further comprises one or more of a thixotropic agent, a dispersant, an anti-wear agent, and an antioxidant; Wherein, the thixotropic agent includes one or more of nano-silica, diatomaceous earth, organic bentonite, polyolefin wax, polyfatty acid amide wax, hydrogenated castor oil, polyamide wax, and vinyl chloride compound; and / or, the dispersant comprises one or more of oleic acid, stearic acid, titanate, and polyether; and / or, the anti-wear agent comprises one or more of graphite, molybdenum disulfide, organic molybdenum compounds, sulfur-phosphorus compounds, chlorophosphorus compounds, chlorosulfur compounds, organic phosphides, and organic metal salts; and / or, the antioxidant comprises one or more of an organophosphorus compound, an organomolybdenum compound, an alkylthiocarbamate zinc, a phenolic compound, and a complex compound; And / or, the base fluid includes one or more of mineral oil, synthetic hydrocarbon oil, ester oil, silicone oil, natural oil, and fluorinated oil.
11. The magnetorheological fluid according to claim 10, characterized in that Based on the total mass of the magnetorheological fluid, The mass proportion of the crystalline magnetic particles and the amorphous magnetic particles is 70% to 85%; And / or, the mass proportion of the base liquid is 10% to 20%; And / or, the mass proportion of the thixotropic agent is 1.0% to 4.0%; And / or, the mass proportion of the dispersant is 0.5% to 3.0%; And / or, the mass proportion of the anti-wear agent is 0.3% to 1.5%; And / or, the antioxidant accounts for 0.3% to 1.5% by mass.
12. The magnetorheological fluid according to any one of claims 7 to 11, characterized in that: The average particle size of the crystalline magnetic particles is 1 μm to 10 μm.
13. A method for preparing the magnetorheological fluid according to any one of claims 7 to 12, characterized in that: The steps include: The magnetorheological fluid is obtained by subjecting a mixture of the amorphous magnetic particles according to any one of claims 1 to 3 or the amorphous magnetic particles prepared by the method for preparing the amorphous magnetic particles according to any one of claims 4 to 6, crystalline magnetic particles, and a base liquid to a second ball milling process.
14. The method for preparing a magnetorheological fluid according to claim 13, wherein: The speed of the second ball milling treatment is 300 rpm to 500 rpm, the treatment time is 2 to 10 hours, and the ball-to-material ratio is (1 to 5):
1.
15. A device, characterized in that: The magnetorheological fluid comprises the magnetorheological fluid according to any one of claims 7 to 12 or the magnetorheological fluid prepared by the preparation method of the magnetorheological fluid according to claim 13 or 14.